Learn Adobe Photoshop Lightroom 3 by video - Grey, Tim (Peachpit Press, 2011)
"This innovative product from Adobe Press offers an incredible 10 hours of high-quality video training teach the fundamentals of Adobe Photoshop Lightroom 3. Experienced instructors Tim Grey and Mikkel Aaland present the video instruction, complete with lesson files. Project files used in the lessons are included so viewers can practice what they've learned. This innovative product from Adobe Press offers an incredible 10 hours of high-quality video training teach the fundamentals of Adobe Photoshop Lightroom 3. Experienced instructors Tim Grey and Mikkel Aaland present the video instruction, complete with lesson files. Project files used in the lessons are included so viewers can practice what they've learned."--Resource description page.
Keywords: Adobe Photoshop lightroom; Photography -- Digital techniques; Photographie numérique; Photography; Digital techniques; Electronic videos